BOOK REVIEWS (Journal of Finance, 1961)
Book reviewed in this article: Business Finance : Financing the Natural Gas Industry . By R ichard W. H ooley . Business Cycle Indicators , Vols. I and II. Edited by G eoffrey H. M oore . Insurance: The Sun Insurance Office, 1710–1960 . By P. G. M. D ickson . Ensuring Medical Care for the Aged . By M ortimer S piegelman . International Finance: The Foreign Tax Credit . By E lisabeth A. O wens . Foreign Exchange in Canada: An Outline . By S idney A. S heperd . Taxation and Operations Abroad: A Symposium Conducted by the Tax Institute . Princeton: Tax Institute, Inc. Money and Banking: Techniques of Monetary Control . By J oseph A schheim . Die Goldmärkte der Welt seit Verlassen des Goldstandards . By H ermann B artels . Il Mercato del denaro di New York . By R enato G uadagnini . Central Banking in Undeveloped Money Markets . By S. N. S en . The Changed Structure: A Different Picture of the Monetary Economy . By M arcel S uchestow . Inflation . By T homas W ilson . Public Finance: Taxation in India . By W. W. B rudno , C. K. C obb , J r ., and N. A. P alkhivala; with the aid of R. M. E igner and L. D. H ollman . The Public Finances: An Introductory Textbook . By J ames M. B uchanan . Public Finance: Needs, Sources, and Utilization . By C onference of the U niversities ‐N ational B ureau C ommittee for E conomic R esearch . Trends in Government Financing . By M orris A. C opeland . Princeton, N.J.: Princeton University Press, 1961. Pp. xxvi+210. $5.00. Personal Deductions in the Federal Income Tax . By C. H arry K ahn . Die Ehegattenbesteuerung . By L ore K ullmer . Financial Administration in Local Government . By A. H. M arshall . Public Finance . By E arl R. R olph and G eorge F. B reak . The Economics of Public Finance . By P hilip E. T aylor . California Local Finance . By J ohn A. V ieg et al . Real Estate Finance: Capital Requirements for Urban Development and Renewal . By J. W. D yckman and R. R. I saacs